Tumour‐associated B cells in urothelial urinary bladder cancer. (10th December 2019) - Zirakzadeh, A. Ali; Sherif, Amir; Rosenblatt, Robert; Ahlén Bergman, Emma; Winerdal, Max; Yang, David; Cederwall, Johanna; Jakobsson, Vivianne; Hyllienmark, Martin; Winqvist, Ola; Marits, Per
Abstract: Tumour infiltrating B cells and CD38 + plasma cells have been correlated with survival in different malignancies but their role in urinary bladder cancer is unclear. IL‐10 is a multifunctional cytokine with both anti‐inflammatory and immunostimulatory properties, that can be released by regulatory B cells (Bregs). We have stained paraffin‐embedded tumour sections from 31 patients with invasive urothelial urinary bladder cancer with respect to CD20 + B cells, CD38 + cells, IL‐10‐expressing cells, IgG, C1q and C3a and analysed the impact of these markers on survival. Interestingly, we observe tumour‐associated CD20 + B cells forming follicle‐like structures in tumours of some patients. We demonstrate that follicle‐like structures, tumour‐associated CD38 + cells, IL‐10 produced by non‐B cells, tumour infiltrating IgG and activation of the complement system, may associate to longer survival of urinary bladder cancer patients. IL‐10 expression by tumour‐associated Bregs may instead negatively affect prognosis. More research is needed to fully understand the role of B cells and IL‐10 in urinary bladder cancer.